Combination of ozonation with GAC, AIX and biochar post-treatment for removal of pharmaceuticals and transformation products from municipal WWTP effluent - Fakioglu, Malhun; Golovko, Oksana; Baresel, Christian; Ahrens, Lutz; Öztürk, İzzet (Royal Society of Chemistry, 2024)
Pharmaceuticals have been detected in water and wastewater, resulting in increasing research attention towards the elimination of these substances from aqueous environments. Due to the limitations of conventional processes in wastewater treatment plants (WWTPs) to fully eliminate these compounds, more research is needed on complementary advanced treatment technologies. This study aims to examine the removal efficiency for 24 selected pharmaceuticals and the fate of their 7 main metabolites including several oxidation transformation products by various technique combinations applied on the effluent from a full-scale WWTP. Investigated treatment options include ozonation (O3) combined with either granular activated carbon (GAC), two different types of biochar, and anion exchange (AIX) in a continuously operated laboratory-scale system. The average removal of analyzed pharmaceuticals ranged between 8.8–97% with an O3 dose of 0.28 g O3/g DOC (dissolved organic carbon), whereas it ranged from 86–99% for higher O3 dosages (0.96 and 2.17 g O3/g DOC). Overall, the investigated metabolites of pharmaceuticals exhibited lower removal efficiency (between −33 and 99%) with ozone compared to the parent compounds at all O3-dosages. Concentrations of oxidation transformation products such as citalopram N-oxide were increased after ozone treatment, whereas it was decreased after the columns at different rates. The bromate concentrations during all three O3-dosages (0.28, 0.96 and 2.17 g O3/g DOC) were below 5 μg L−1. GAC was the best performing sorbent among all materials, where even after two weeks of continuous operation, nearly all compounds were removed below quantification levels. Although biochar 1 showed better performance (30–89%, mean = 68%) than biochar 2 (8.5–82%, mean = 38%), both sorption materials showed reduced sorption capacity over the time period of two weeks for most of the target compounds. On the other hand, AIX had lower removal rates ranging between 2–55% (mean = 20%). Regarding the combination of O3 with the individual sorbent materials, GAC was the most successful combination with O3 for the removal of pharmaceuticals (>99%) and oxidation transformation products (>60%). The combination of O3 with biochar 1 was more successful (mean = 91%) than the combination with biochar 2 (mean = 79%), where the combination of O3 with AIX showed the lowest removal rates (mean = 58%).
Keywords: wastewater; wastewater treatment plants; pharmaceuticals; ozonation; wastewater treatment